2012
DOI: 10.1152/ajpcell.00503.2010
|View full text |Cite
|
Sign up to set email alerts
|

Small conductance potassium channels drive ATP-activated chloride secretion in the oviduct

Abstract: Keating N, Quinlan LR. Small conductance potassium channels drive ATP-activated chloride secretion in the oviduct. Am J Physiol Cell Physiol 302: C100 -C109, 2012. First published September 14, 2011; doi:10.1152/ajpcell.00503.2010.-The molecular mechanisms controlling fluid secretion within the oviduct have yet to be determined. As in other epithelia, both secretory and absorptive pathways are likely to work in tandem to drive appropriate ionic movement to support fluid movement across the oviduct epithelium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Purinergic signalling via P2Y 2 receptors also constitutes a key mechanism for regulating chloride secretion and thus fluid formation in the bovine oviduct [193]. In a later paper, they claimed that purinergic activation of a calcium-dependent, apaminsensitive potassium conductance was essential to promote chloride secretion [194].…”
Section: Fallopian (Uterine) Tubes/oviductmentioning
confidence: 99%
“…Purinergic signalling via P2Y 2 receptors also constitutes a key mechanism for regulating chloride secretion and thus fluid formation in the bovine oviduct [193]. In a later paper, they claimed that purinergic activation of a calcium-dependent, apaminsensitive potassium conductance was essential to promote chloride secretion [194].…”
Section: Fallopian (Uterine) Tubes/oviductmentioning
confidence: 99%
“…Both of the top SNPs in Holstein (rs134910746) and Jersey (rs29020504) populations on the interval extended from 15.8 to 16.0 Mbp on BTA 3 were found to be inside intronic regions of potassium intermediate/small conductance calcium-activated channel, subfamily N, member 3 ( KCNN3 ) gene. KCCN3 plays a key role in fluid secretion within the bovine oviduct which is essential to provide an appropriate environment for gamete maturation, transport, fertilization and early embryo development [ 45 ]. It has also been shown that KCNN3 is differentially expressed between oocytes and granulosa cells (GCs) during development of the sheep ovarian follicle [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect was mediated by activation of P2Y 2 or possibly P2Y 4 receptors (Cox and Leese, 1994;Villalon et al, 1995) located on the basal surface of the cells; it involved a rapid increase in Ca 2+ i due to Ca 2+ mobilization (Cox and Leese, 1994;Villalon et al, 1995;Dickens et al, 1996;Anon. ;Squires et al, 1995;Tiemann et al, 1996) and activation of Ca 2+ -dependent, apaminsensitive K + conductance (Keating and Quinlan, 2012). This mode of purinergic regulation of fluid and solutes secretion is common in secretory epithelia (Novak, 2008;Burnstock, 2014b).…”
Section: Fallopian Tubementioning
confidence: 99%